The use of rural areas in Portugal: historical perspective and the new trends - Almeida, M. A. (Revista Galega de Economía, 2020)
The Portuguese landscape and its rural areas are the result of thousands of years of human presence, particularly since the late nineteenth century, when protectionist public policies were put in place to promote food self-sufficiency. During the Estado Novo regime, four main agricultural policies were enforced: wheat campaigns, internal colonization, agricultural hydraulic systems and reforestation. Nevertheless, there was a massive rural exodus, starting mainly in the 1960s, which resulted in the depopulation of 80 per cent of the territory. Nowadays, less than 20 per cent of the Portuguese population inhabits interior regions. This demographic change presents huge socio-economic challenges. Recently there have been new trends, based on land concentration and super intensive monoculture, which are incompatible with central and local governments’ policies and strategies to reverse depopulation. The sustainability of Portugal’s rural world, its landscape and the quality of life of its population are at risk. Four items were identified in this article: eucalyptus and pine forests, olive plantations, greenhouses and mining.